2022
DOI: 10.1016/j.iot.2021.100399
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual IoT-based early-warning architecture for remote monitoring of COVID-19 patients in wards and at home

Abstract: Due to the COVID-19 pandemic, health services around the globe are struggling. An effective system for monitoring patients can improve healthcare delivery by avoiding in-person contacts, enabling early-detection of severe cases, and remotely assessing patients’ status. Internet of Things (IoT) technologies have been used for monitoring patients’ health with wireless wearable sensors in different scenarios and medical conditions, such as noncommunicable and infectious diseases. Combining IoT-related technologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 70 publications
1
32
0
Order By: Relevance
“…Although the positive findings on NEWS as a predictor of outcomes in this paper echo with much of the international literature on this subject (Paganelli et al, 2021;Paixão-Cortes et al, 2021;Stocker et al, 2021), the introduction of EWSs to care homes requires an understanding of the problems they can be used to address and what their adverse consequences might be. The clinical context of a care home is very different to that of an acute hospital ward, where EWS systems are usually employed.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Although the positive findings on NEWS as a predictor of outcomes in this paper echo with much of the international literature on this subject (Paganelli et al, 2021;Paixão-Cortes et al, 2021;Stocker et al, 2021), the introduction of EWSs to care homes requires an understanding of the problems they can be used to address and what their adverse consequences might be. The clinical context of a care home is very different to that of an acute hospital ward, where EWS systems are usually employed.…”
Section: Discussionsupporting
confidence: 61%
“…Comas-Herrera et al ( 2020) have reported that, in a survey of 22 countries, 41% of deaths from COVID-19 occur in care homes. Systems based on NEWS2 scoring have been found to be an effective predictor of outcome in many countries including Italy (Paganelli et al, 2021), Brazil (Paixão-Cortes et al, 2021 and Norway (Myrstad et al, 2020) as well as in the UK (Stocker et al, 2021).…”
mentioning
confidence: 99%
“…Paganelli et al [12] also proposed similar work. They used the data from the IoT and matched the result with the earlywarning score which has been commonly used in hospital, such as NEWS-2 [8].…”
Section: Related Workmentioning
confidence: 82%
“…The whole system is connected to android interface through API to track the recovery and health condition of recovered patient [21]. A similar framework proposed by Paganelli et al discussed various architecture utilization for monitoring of COVID-19 patients that could assist in detecting the COVID-19 [22]. The proposed architecture includes three layers mainly i.e.…”
Section: Related Workmentioning
confidence: 99%